Nightlights - Alvarez, Lorena (Nobrow, 2019)
Each night a young girl named Sandy captures the lights that come into her bedroom and turns them into wonderful creatures to play with in her dreams. The next day, in lieu of schoolwork, Sandy spends her days drawing the magnificent creations from her dreams. Then a mysterious new girl with pale skin and purple hair comes to school and takes an interest in Sandy and her drawings. Sandy is excited to be her friend, but things take a sinister turn when the girl begins controlling Sandy and her drawings.